An examination of Australian newspaper coverage of the link between alcohol and cancer 2005 to 2013 - Jaklin Eliott; Andrew John Forster; Joshua McDonough; Kathryn Bowd; Shona Crabb (BMC, 2017)
Abstract Background Alcohol is a Class-1 carcinogen but public awareness of the link between alcohol and cancer is low. The news media is a popular, readily-accessible source of health information and plays a key role in shaping public opinion and influencing policy-makers. Examination of how the link between alcohol and cancer is presented in Australian print media could inform public health advocacy efforts to raise awareness of this modifiable cancer risk factor. Method This study provides a summative qualitative content analysis of 1502 articles that included information about a link between alcohol and cancer, as reported within Australian newspaper media (2005-2013). We use descriptive statistics to examine the prominence of reports, the nature and content of claims regarding the link between alcohol and cancer, and the source of information noted in each article. Results Articles were distributed throughout newspapers, most appearing within the main (first) section. The link between alcohol and cancer tended not to appear early in articles, and rarely featured in headlines. 95% of articles included a claim that alcohol causes cancer, 5% that alcohol prevented or did not cause cancer, 1% included both. Generally, the amount of alcohol that would cause or prevent cancer was unspecified or open to subjective interpretation. Coverage increased over time, primarily within community/free papers. The claim that alcohol causes cancer often named a specific cancer, did not name a specific alcohol, was infrequently the focus of articles (typically subsumed within an article on general health issues), and cited various health-promoting (including advocacy) organisations as information sources. Articles that included the converse also tended not to focus on that point, often named a specific type of alcohol, and most cited research institutions or generic 'research' as sources. Half of all articles involved repetition of materials, and most confirmed that alcohol caused cancer. Conclusions Information about a link between alcohol and cancer is available in the Australian newsprint media, but may be hidden within and thus overshadowed by other health-related stories. Strategic collaboration between health promoting organisations, and exploitation of 'churnalism' and journalists' preferences for ready-made 'copy' may facilitate increased presence and accuracy of the alcohol-cancer message.